2017
DOI: 10.1186/s13256-017-1308-1
|View full text |Cite
|
Sign up to set email alerts
|

Segmental testicular infarction: a case report

Abstract: BackgroundSegmental testicular infarction is a very rare condition, which can mimic a testicular torsion or testicular cancer. Correct diagnosis is difficult but it is important to avoid unnecessary radical treatment.Case presentationWe report a clinical case of a 36-year-old white man who presented at our emergency department with subacute testicular pain. A urine analysis, Doppler ultrasound, surgical exploration, blood analysis, and magnetic resonance imaging were performed to diagnose his condition, to exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The pathogenesis is still not well known and is usually idiopathic 8 . Reduced or interrupted blood flow, insufficient collateral blood supply, and thrombus formation is one of proposed mechanisms [9][10][11] . Epididymo-orchitis is a one of the well-known underlying causes 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis is still not well known and is usually idiopathic 8 . Reduced or interrupted blood flow, insufficient collateral blood supply, and thrombus formation is one of proposed mechanisms [9][10][11] . Epididymo-orchitis is a one of the well-known underlying causes 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler will show reduced or absent flow within the area of infarction. 5 There is a broad spectrum of testicular pathologies that share similar clinical symptoms making segmental testicular infarction difficult to distinguish from other findings. Because the sonographic presentation of testicular masses or testicular torsion are similar, these are the two most common differential diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually clinically present with acute scrotal pain and swelling; however, some studies have found that these symptoms may be variable or absent. 5 Physical examinations of the testis are typically normal without a palpable mass. Sonography of the testicles using color and pulsed wave Doppler is important for making a diagnosis of segmental infarctions.…”
Section: Discussionmentioning
confidence: 99%
“…Initial onset can be similar to that of testicular torsion, with a sudden and lacerating pain, but it is also described in patients with falciform anemia or septic embolus during bacterial endocarditis. (37) with panic attacks. (41,42)…”
Section: Subgroup 5: Vascular Causesmentioning
confidence: 99%